Spinoza and architectural thinking. Issue 3 (2nd July 2020) - Lord, Beth
ABSTRACT: Although Spinoza makes few remarks about architecture, his use of architectural examples, understood in the context of his metaphysics and theory of knowledge, reveal the architect to be a distinctive kind of human thinker. In this paper I explore the kind of thinking the architect does, first by demonstrating that Spinoza distinguishes the architect's adequate way of conceiving a building from inadequate ways of imagining one, and second by considering how Spinoza might have understood the architect to translate that adequate thinking into the practice of building and construction. I argue that for Spinoza, the architect integrates imaginative, rational, and intuitive thinking, and the parallel forms of bodily action, to understand and construct a building in its causal connections to its component materials, environment, and users. To understand the true idea of a building is therefore to understand its embeddedness in the world and its functional place in a network of modal relations.